Step-by-step explanation:
LHS = Left Hand Side ; RHS = Right Hand Side
a) RHS = 1/ tan x
= 1/ (Sin x/Cos x)
= Cos x/Sin x
= LHS
b) LHS = Sin^2 x / tan^2 x
= Sin^2 x / (Sin^2 x/Cos^2 x)
=( Sin^2 x * Cos^2 x) / (Sin^2 x)
= Cos^2 x
= 1 - Sin^2 x (Because sin^2 x + cos^2 x = 1)
= RHS
c) RHS = Sin^3 x / tan x + Cos^3 x
= Sin^3 x / (Sinx/Cosx) + Cos^3 x
= (Sin^3 x * Cos x)/Sin x + Cos^3 x
= Sin^2 x * Cos x + Cos^3 x
= Cos x (Sin^2 x + Cos^2 x)
= Cos x *(1) {Because, Sin^2 x + Cos^2 x = 1}
= Cos x
= LHS